2018
DOI: 10.1001/jama.2018.7498
|View full text |Cite
|
Sign up to set email alerts
|

Screening for Osteoporosis to Prevent Fractures

Abstract: IMPORTANCE By 2020, approximately 12.3 million individuals in the United States older than 50 years are expected to have osteoporosis. Osteoporotic fractures, particularly hip fractures, are associated with limitations in ambulation, chronic pain and disability, loss of independence, and decreased quality of life, and 21% to 30% of patients who experience a hip fracture die within 1 year. The prevalence of primary osteoporosis (ie, osteoporosis without underlying disease) increases with age and differs by race… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
128
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 485 publications
(132 citation statements)
references
References 32 publications
1
128
1
2
Order By: Relevance
“…In the absence of an international consensus on fracture risk screening [2,4,5,30], we chose to use the assessment and management clinical algorithm developed by NOGG [3], since a screening program similar to the NOGG screening strategy is supported by randomized controlled trial evidence [9]. The NOGG screening strategy uses 10-year absolute probability of fracture as calculated by FRAX and suggests treatment or reassurance based on thresholds of risk, which are age dependent and consider competing risks.…”
Section: Genomic Screening In Fracture Risk Screeningmentioning
confidence: 99%
See 1 more Smart Citation
“…In the absence of an international consensus on fracture risk screening [2,4,5,30], we chose to use the assessment and management clinical algorithm developed by NOGG [3], since a screening program similar to the NOGG screening strategy is supported by randomized controlled trial evidence [9]. The NOGG screening strategy uses 10-year absolute probability of fracture as calculated by FRAX and suggests treatment or reassurance based on thresholds of risk, which are age dependent and consider competing risks.…”
Section: Genomic Screening In Fracture Risk Screeningmentioning
confidence: 99%
“…Osteoporosis is a common and costly disease that results in an increased predisposition to fractures [1]. Many guidelines [2][3][4][5][6] aimed at the prevention of osteoporosis-related fractures incorporate the Fracture Risk Assessment Tool (FRAX) [7,8], a validated method to risk stratify individuals for treatment by assessing their 10-year probability of major osteoporotic fracture. Guidelines vary widely, but often recommend a staged process where individuals are first assessed with a clinical-risk-factor-based FRAX (CRF-FRAX), and those at increased risk of fracture are then additionally characterized with a more expensive bone mineral density (BMD)-based FRAX (BMD-FRAX) score.…”
Section: Introductionmentioning
confidence: 99%
“…treat osteoporosis early to prevent fractures. 2 Available evidence on screening and treatment in women and men were reviewed with the intention of updating the 2011 USPSTF recommendations. The review also evaluated risk assessment tools, screening intervals, and effi cacy of screening and treatment in various subpopulations.…”
Section: Moreno and Colleaguesmentioning
confidence: 99%
“…This is equivalent to the fracture risk of a 65-year-old white woman with no major risk factors for fracture (grade B recommendation-high certainty that the benefi t is moderate, or moderate certainty that the benefi t is moderate to substantial). 2…”
Section: Moreno and Colleaguesmentioning
confidence: 99%
“…Vitamin Coriented foods comprise one of the most important components of the diet and have been reported to exert many potential health benefits, because they are rich in vitamins, fiber, phytochemicals, and minerals (6). Several studies have found that DIVCF significantly lowers the risk of breast cancer, hypertension, metabolic syndrome, type 2 diabetes mellitus, depression, inflammatory bowel disease, and all-cause mortality (7,8). Antioxidants and anti-inflammatory components from such diets are hypothesized to play a vital role in the protective effects against osteoporosis (9).…”
Section: Introductionmentioning
confidence: 99%